Breeding Sites of Aedes aegypti: Potential Dengue Vectors in Dire Dawa, East Ethiopia - Getachew, Dejene; Tekie, Habte; Gebre-Michael, Teshome; Balkew, Meshesha; Mesfin, Akalu (Interdisciplinary Perspectives on Infectious Diseases, 2015)
Background and Objectives. Entomological survey was carried out from May-June to September-October 2014 to investigate the presence of dengue vectors in discarded tires and artificial water containers in houses and peridomestic areas. Methods. A cross-sectional immature stage survey was done indoors and outdoors in 301 houses. Mosquito larval sampling was conducted using pipette or dipper depending on container types. Larvae were identified morphologically and larval indices were also calculated. Results. A total of 750 containers were inspected, and of these 405 were positive for mosquito larvae. A total of 1,873 larvae were collected and morphologically identified as Aedes aegypti (n=1580: 84.4%) and Culex (n=293: 15.6%). The larval indices, house index, container index, and breteau index, varied from 33.3 to 86.2, from 23.2 to 73.9, and from 56.5 to 188.9, respectively. Conclusion. Aedes aegypti is breeding in a wide range of artificial containers. To control these mosquitoes, the integration of different methods should be taken into consideration.